2020
DOI: 10.1007/s00784-020-03240-5
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of growth factors for the treatment of peri-implant diseases: a systematic review and meta-analysis

Abstract: The aim of this study was to conduct a systematic review and meta-analysis on the efficacy of growth factors (GF) on clinical outcomes after treatment (surgical/non-surgical) of peri-implant diseases (peri-implant mucositis and peri-implantitis). MATERIALS AND METHODS A protocol was developed to answer the following focused question: Is there any difference for the use of GF for treatment of peri-implant diseases versus comparative GF treatment or without GF? Electronic database and manual searches were indepe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 71 publications
1
8
0
Order By: Relevance
“…Many studies have already assessed the efficacy of probiotics in preventing caries, gingivitis, cancer therapy-induced oral mucositis, periodontitis, and peri-implant diseases, which are related to bacterial biofilm and host immune response. The results support the potential use of probiotics in managing gingivitis, cancer therapy-induced oral mucositis, and periodontitis [17][18][19][20] .…”
supporting
confidence: 68%
“…Many studies have already assessed the efficacy of probiotics in preventing caries, gingivitis, cancer therapy-induced oral mucositis, periodontitis, and peri-implant diseases, which are related to bacterial biofilm and host immune response. The results support the potential use of probiotics in managing gingivitis, cancer therapy-induced oral mucositis, and periodontitis [17][18][19][20] .…”
supporting
confidence: 68%
“…Regeneration stimulating factors include platelet-derived factors, such as platelet-rich fibrin (PRF), plasma rich in growth factors (PRGF), and enamel matrix derivative (EMD). In the following section, the most promising therapeutic options are shortly described (19). Unfortunately, the evidence of systematic reviews is still scarce.…”
Section: Question 5: Should We Apply Additional Biologicals or Stem Cmentioning
confidence: 99%
“…While we can rely on a lot of positive evidence in the use of PRF in periodontology, available data on peri-implant regeneration are very limited (41). PRF-membranes in one randomized controlled clinical trial have been shown to be inferior to collagen membranes (19). The adjunctive use of PRF to OFD showed beneficial outcomes in terms of clinical attachment level (CAL) after 3 and 6 months (19).…”
Section: Autologous Platelet Concentratesmentioning
confidence: 99%
See 2 more Smart Citations